2000
DOI: 10.1038/labinvest.3780183
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Localization of Neutral Endopeptidase 24.11/CD10 in Human Gestational Trophoblastic Diseases

Abstract: SUMMARY:Neutral endopeptidase 24.11 (NEP)/CD10 is a cell-surface peptidase that hydrolyzes various bioactive peptides.NEP is distributed in both normal and neoplastic cells and plays a functional role by modulating cellular responses to peptide substrates. Recently, NEP has been shown to be expressed in normal placental trophoblasts, suggesting its physiological role during pregnancy. In the present study, we investigated the expression of NEP in hyperplastic and anaplastic trophoblasts in gestational trophobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although leukemia inhibitory factor plays an important role in implantation and placentation in several species, the paracrine role of leukemia inhibitory factor in the biology of human implantation site intermediate trophoblastic cells is not known. Those intermediate trophoblastic cells also express CD10, a neutral endopeptidase [64,122].…”
Section: Gene Expression and Immunohistochemical Features Of Trophoblastic Subpopulationsmentioning
confidence: 99%
“…Although leukemia inhibitory factor plays an important role in implantation and placentation in several species, the paracrine role of leukemia inhibitory factor in the biology of human implantation site intermediate trophoblastic cells is not known. Those intermediate trophoblastic cells also express CD10, a neutral endopeptidase [64,122].…”
Section: Gene Expression and Immunohistochemical Features Of Trophoblastic Subpopulationsmentioning
confidence: 99%
“…Contrary to P-LAP or A-LAP, DPPIV, the aminopeptidase cleaving certain chemokines, was selectively expressed in the noninvasive phenotype EVTs, and down-regulation of DPPIV was associated with EVT invasion . Our previous studies also showed that neutral endopeptidase (NEP), another peptidase degrading endothelin-1 that is one of the peptides promoting EVT invasion (Chakraborty et al, 2003), was expressed in differentiated syncytiotrophoblasts but not in invasive EVTs (Ino et al, 2000;Uehara et al, 2001). Thus, whether these peptidases function as a positive or negative regulator of the invasiveness of EVT appears to be dependent on the type of target peptide sub- …”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed using the avidin-biotin immunoperoxidase technique as described previously (Ino et al, 2000). Sections were cut at a thickness of 4 m. For heat-induced epitope retrieval, deparaffinized sections in 0.01 M citrate buffer were treated three times for 5 minutes at 95°C in a microwave oven.…”
Section: Immunohistochemistrymentioning
confidence: 99%